2016
DOI: 10.1002/pssb.201600077
|View full text |Cite
|
Sign up to set email alerts
|

The cluster architecture of carbon in polymer nanocomposites observed by impulse acoustic microscopy

Abstract: physica s s p status solidi b 1956 V. Levin et al.: The cluster architecture of carbon in polymer nanocomposites ß

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…The images are formed in an ultramicroscopic mode —sizes of some scatterers could be smaller than the wavelength; the presence of air in the conglomerates results in a high efficiency of ultrasonic scattering; according to estimations , conglomerates are effective scatterers. It has been revealed that both graphite nanoparticles (GNP) and nanotubes (MWCNT) possess a strong tendency to agglomeration . Depending on the filler content these agglomerates are formed and distributed over the material bulk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The images are formed in an ultramicroscopic mode —sizes of some scatterers could be smaller than the wavelength; the presence of air in the conglomerates results in a high efficiency of ultrasonic scattering; according to estimations , conglomerates are effective scatterers. It has been revealed that both graphite nanoparticles (GNP) and nanotubes (MWCNT) possess a strong tendency to agglomeration . Depending on the filler content these agglomerates are formed and distributed over the material bulk.…”
Section: Resultsmentioning
confidence: 99%
“…Impulse acoustic microscopy is based on using focused ultrasonic beams and the raster principle of image formation . A focused ultrasonic beam interacts with a plane‐parallel object within its waist.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulty of volume imaging of all common methods remains in receiving of low magnitudes or detecting of small differences of signals. Efficiency of ultrasound scattering at small‐size elements depends on acoustic impedance ratio between immersion liquid and scatterer . In the decellularized lung samples, the protein elements without cell content have slightly higher acoustic impedance and amplitude of back‐scattered signal (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Experimental setup of SIAM‐2011 is shown in Figure . The method is described in detail in previous works . We used common regime of imaging—C‐scanning which presents internal microstructure in the form of layer‐by‐layer images of horizontal cross‐sections at different depths (Figure ); and modified B/D‐mode (brightness/depth) which images internal microstructure in vertical section.…”
Section: Methodsmentioning
confidence: 99%